Frequency of Y Chromosome Microdeletions Among Iranian Infertile Men with Azoospermia and Severe Oligozoospermia: A Meta-analysis - Yousefi-Razin, Ehsan (J Reprod Infertil, 2016)
BACKGROUND: While multiple factors can contribute to male infertility, genetic factors, such as chromosomal disorders or Y-chromosome microdeletion, are responsible for about 10% of male infertility. Considering the role of Y-chromosome micro-deletions in men with oligozoospermia who volunteer for in vitro fertilization (IVF), the prevalence of such microdeletions in each particular community needs to be exactly determined. Hence, the present study attempted to analyze the available literature on the frequency of chromosome microdeletion among Iranian infertile men. METHODS: In the first stage, a systematic search was performed on international and Iranian databases including PubMed, Scopus, Web of Science, IranMedex, MEDLIB, and Scientific Information Database in order to extract all relevant studies published until December 1, 2014. RESULTS: According to the literature review and meta-analysis process, Y chromosome microdeletions were present in about 12.1% (95% CI, 6.5–21.5) of Iranian infertile men with azoospermia and severe oligozoospermia. CONCLUSION: Because of the presence of Y-chromosome microdeletion in at least 12% of Iranian infertile men, it is necessary all the IVF centers, implement this Y-chromosome microdeletion screening tests in the work-up of male infertility.